Predicting the conversion of laparoscopic to open cholecystectomy:an experience in a tertiary care hospital of central India - Singh, Ashish Pratap; Sharma, Priyank; M, Sajith Babu S.; Gaharwar, A.P. S. (International Surgery Journal, 2016)
Background: Laparoscopic cholecystectomy is the gold standard procedure for symptomatic cholelithiasis. However some laparoscopic cholecystectomies need to be converted into an open cholecystectomy for various reasons. So it will be very helpful if criteria can be developed for the prediction of difficult laparoscopic cholecystectomies. The objective of this study was to evaluate pre-operative risk factors amounting to the conversion of laparoscopic cholecystectomy into an open cholecystectomy. Methods: This is a prospective study in which 255 patients presenting with definitive diagnosis of cholelithiasis meeting the inclusion criteria, undergoing laparoscopic cholecystectomy were included in the study. Their demographic data, symptomatology and associated illness were documented. Results: Out of 255 patients 19 (7.4%) patients required conversion to open cholecystectomy. In converted group of patients, 73.33% patients were more than 50 years , 52.63% had BMI more than 30, 68.42% had >2 episodes of cholecystitis, 63.16% had leukocytosis, 68.42% had gallbladder wall thickness >3 mm, 63.16% had pericholecystic collection. Conclusions: Clinical and ultrasonographic factors can help to predict difficult laparoscopic cholecystectomy and likelihood of conversion of laparoscopic cholecystectomy to open surgery.